SINTESIS SELULOSA DIASETAT DARI ECENG GONDOK (Eichhornia crassipes) DAN POTENSINYA UNTUK PEMBUATAN MEMBRAN - Richa Rachmawaty; Metty Meriyani; Slamet Priyanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Water hyacinth population that continues to grow every day becomes a problem that must be solve immediately. One of the prospective utilization is synthesis cellulose diacetate based on cellulose which containing in water hyacinth. The purpose of this research are to determine the potential of water hyacinth in the manufacture of membranes and determine the effect of polymer concentration and evaporation time on membrane performance. In this research, there were two series of experiments, synthesis of cellulose diacetate from water hyacinth and manufacture of membranes. Synthesis cellulose diacetate was done by two steps, cellulose insulation and cellulose acetylation. While, manufacture of membranes was done by phase inversion method, where the parameters that will be examined is the optimization point of polymer concentration 13, 14 and 15% weight as well as evaporation time 0, 5, 10 and 15 seconds. Cellulose diacetate used as polymer, with acetone as solvent and polyethylene glycol (PEG) as additives. Characterization of membrane was done by measuring flux and rejection to separate humic acid water, and analysis using FTIR and SEM. The results showed that water hyacinth can be utilized as cellulose diacetate and has potential to be used as membranes. In addition, it can be concluded that the concentration of polymer and evaporation time have an affect to the performance of the membrane where the greater concentration of the polymer and the longer of the evaporation time caused the morphological structure of the membrane will be more dense and pores become smaller, so flux getting smaller while the rejection getting larger. Membrane with 15 %wt polymer concentration and 10 seconds evaporation time produces the best performance with flux 460,54 L/m2.hour and rejection 64,28%.